Diagnosis dan Tatalaksana Edema Paru Kardiogenik - Nora Zulfa; Emelda Emelda (Lembaga Pengembangan Kinerja Dosen, 2024)
Cardiogenic acute pulmonary edema is a medical emergency that requires early detection and prompt management. This condition is characterized by symptoms of acute heart failure accompanied by hypoxia. This is caused by fluid accumulation in the interstitial space of the lungs, making it difficult to exchange O2 and CO2 due to increased pulmonary capillary pressure. A 72-year-old man was reported to have acute heart failure leading to acute pulmonary edema which was caused by his acute coronary syndrome. Physical examination found blood pressure 160/100, pulse 105 x/min, respiration 42 x/min, jugular venous pressure 5+5 cmH2O, thorax found ronkhi sound (+/+), and oedema extremities. Thoracic X-ray examination found bat-wing appearance, electrocardiography found pathological Q. II-III-aVF and T. Inversion V4-V6, I-aVL, troponin 1.02 ng/mL. Immediate management was given with the target of reducing morbidity and mortality.